Gamification and ai in english language training for nurses: Trends and outcomes - Sukmawati Ida Dian; Setyawati Martyarini Budi; Prasetio Agung Budi (BIO Web of Conferences)
The purpose of this systematic literature review (SLR) is to investigate how gamification and artificial intelligence can be included into nursing students’ English language instruction. English language competency has grown in importance for nurses, particularly in the global healthcare setting where precise documentation and efficient communication are essential. However, busy schedules frequently make it difficult for nursing students to find time for language study, which frequently results in lower motivation and engagement during the learning process. Gamification has been shown to be successful in raising motivation and learning engagement through components like leaderboards, badges, and points. AI makes it possible to customize learning by creating materials according to each student’s need and giving them immediate feedback, which might help them become more proficient in the language. This research synthesizes studies on the use of these technologies in nursing education, identifies key trends, evaluates learning outcomes, and discusses challenges such as limited access to technology and lack of training for teachers. The results show that gamification and AI have great potential in improving nursing students’ English competency, especially in enhancing their professional communication skills.